Experimental and numerical assessment of oblique loading quasi-static testing of railway anticlimbers. (February 2021) - Moreno, C; Reid, S; Williams, T
An oblique loading angle test was devised in order to subject the anticlimbers of railway vehicles to a predetermined perpendicular load as well as a predetermined bending moment. The motivation for this type of test was the Standard and industry requirements for anticlimbing devices to prevent overriding and resist a determined perpendicular force while dissipating energy. Anticlimbing units, based on shrinking circular deformation tubes, were subjected to compression tests. The oblique loading was applied by placing the anticlimbing unit on a plate at an angle to the centreline of the unit. A numerical model was validated against the test results, in order to infer the bending moment subjected to the anticlimber unit. The bending moment on the anticlimbers was expected to be fully determined by the perpendicular force and the length of the tube. The predicted bending moment measured by the validated numerical model was smaller than anticipated and was potentially unpredictable. The discrepancy was caused by the irregular distribution of the normal force at the interface of the test machine and the anticlimber head. As a result, the devised angle test was proved unsuitable to induce a consistent and predictable bending moment on the anticlimber units of railway vehicles.